A note on the Tullock dissipation rate - Fabella, Raul V.
We show, among other results, that the Tullock dissipation rate at a symmetric Nash equilibrium, under risk aversion, approaches the risk-neutral rate as rent size becomes small. Under quadratic risk-averse utility, the risk-neutral rate applies under duopoly regardless of rent size. Under constant absolute risk aversion, the rate rises with rent size.
A copy is also available at the UPSE Library Archives (Faculty Publications).
Keywords: Rent seeking; Tullock dissipation rate